“Bacteroides nordii” sp. nov. and “Bacteroides salyersae” sp. nov. Isolated from Clinical Specimens of Human Intestinal Origin - Song, Y. L. (American Society for Microbiology, 2004)
Two groups of unknown bacteria, which phenotypically resemble members of the Bacteroides fragilis group but phylogenetically display >5% 16S rRNA gene sequence divergence from their nearest validly described species, Bacteroides thetaiotaomicron, were characterized by phenotypic and molecular taxonomic methods. Phylogenetically and phenotypically, the unidentified bacteria displayed a relatively close association with each other. However, a 16S rRNA gene sequence divergence of approximately 4% between the two unknown bacteria, as well as distinguishable biochemical characteristics, demonstrates that these organisms are genotypically and phenotypically distinct, and each group may represent a previously unknown subline within the Bacteroides phylogenetic cluster. Subsequent DNA-DNA hybridization studies confirmed that the two novel organisms were indeed distinct from each other. The previously described species closest to both of them is B. thetaiotaomicron (approximately 94% sequence similarity), but they can be differentiated easily from B. thetaiotaomicron by virtue of not utilizing trehalose. DNA-DNA pairing studies also documented the separateness of the unknown species and B. thetaiotaomicron. Based on the phenotypic and phylogenetic findings, two new species, “Bacteroides nordii” sp. nov. and “Bacteroides salyersae” sp. nov, are proposed. The G+C content of the DNA is 41.4 mol% for Bacteroides nordii and 42.0 mol% for Bacteroides salyersae. The type strains of Bacteroides nordii and Bacteroides salyersae are WAL 11050 (ATCC BAA-998 or CCUG 48943) and WAL 10018 (ATCC BAA-997 or CCUG 48945), respectively.